Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1350650118768310
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the oil transport and starvation of piston ring pack

Abstract: In order to accurately predict the lubricant film thickness and generated friction in any tribological contact, it is important to determine appropriate boundary conditions, taking into account the oil availability and extent of starvation. This paper presents a two-dimensional hydrodynamic model of a piston ring pack for prediction of lubricant film thickness, friction and total power loss. The model takes into account starvation caused by reverse flow at the conjunctional inlet wedge, and applied to a ring p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Furthermore, it should be pointed out that only a portion of oil film supplying to the compression ring-cylinder liner system will be transported into the lubrication zone [ 55 ], and some amount of oil film existing the lubrication zone will be remained at the outlet of the lubrication zone during the operation of the compression ring-cylinder liner system [ 56 ]. Hence, some amount of the oil film will be accumulated at the inlet and outlet of the lubrication zone [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it should be pointed out that only a portion of oil film supplying to the compression ring-cylinder liner system will be transported into the lubrication zone [ 55 ], and some amount of oil film existing the lubrication zone will be remained at the outlet of the lubrication zone during the operation of the compression ring-cylinder liner system [ 56 ]. Hence, some amount of the oil film will be accumulated at the inlet and outlet of the lubrication zone [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it should be pointed out that only a portion of oil film supplying to the compression ring-cylinder liner system will be transported into the lubrication zone [ 55 ], and some amount of oil film existing the lubrication zone will be remained at the outlet of the lubrication zone during the operation of the compression ring-cylinder liner system [ 56 ]. Hence, some amount of the oil film will be accumulated at the inlet and outlet of the lubrication zone [ 55 , 56 ]. In order to predicted the transition between fully flooded and starved lubrication conditions in an engine cycle with consideration of the oil film accumulation, an oil transport model [ 56 ] with front and back control volumes at the inlet and outlet of the lubricated zone is employed to calculate the width of lubrication zone, as shown in Fig 5 .…”
Section: Methodsmentioning
confidence: 99%
“…They concluded a thermomixed lubrication model, showing that cavitation flow has a dominant role in load-carrying capacity under high engine speeds. Bewsher et al [16] also observed that oil availability can create starvation in the contact due to the reverse flow and the lack of oil. They found that this effect may lead to increased friction and low lubricant films.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the ring cannot be completely covered by the oil film in the moving direction (ie, the axial direction). It means that a starved lubrication condition will be encountered in the engine cycle besides the fully flooded lubrication condition . Furthermore, when the ring‐liner conjunction is under the starved lubrication condition, the degree of oil starvation is time‐varying because the oil film supplied to the conjunction is non‐uniformly distributed on the liner and the clearance between the ring and liner is time‐varying .…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Furthermore, during the operation of the textured ring‐liner conjunction, the oil film supplied to the conjunction does not flow into the lubrication zone adequately, and some amount of the oil film will be accumulated at the inlet of the lubrication zone . In particular, when the oil film supplied to the conjunction is sufficient, the leading edge of the textured ring is fully flooded, and the oil film accumulation will be observed at the leading edge of the textured ring (in this case, the inlet of lubrication zone is coincide with the leading edge of the textured ring), as shown in Figure a.…”
Section: Mathematical Modelingmentioning
confidence: 99%